The Effect of Educational Tools Exercises on Certain Joints’ Angles in Javelin Performance and Achievement - Mohammed Jasim Mohammed Al-Khalidi (Journal of Global Pharma Technology, 2017)
The study included a number of axes that concentrated on selecting the exercises used in the educational process by the physical education professors and mixing them using wires and plastic nets. These methods help achieving the goals of the educational exercises. The educational exercises included all the technical stages of the Javelin, and have simultaneously concentrated on its difficult aspects, since some of the stages require more than spears and medical balls, but rather tools that help the students learn the initial applications from holding the javelin to the release step, and help the students be precise with the track of the spear through the movement of the plastic, spear-like sticks in certain measurements through parallel-fixed wires, and curved-fixed as well. These tracks well help the students focus on how to perform in the technical stages without much thinking about carrying the tools or the gravity, and concentrate on struggling with steering the spear while running. After mastering the fixed tracks, the Javelin is now performed on the plastic nets. Then, the students do the Javelin using the legal tools on the legal field. The educational exercises along the helping tools were applied on the experiment group for four weeks, an average of two educational units per week. Then it was compared with the original group, and as the statistics show, the experimental group has exceeded the original group.Keywords: Educational exercises, Educational tools, Kinetic variables, Learning to perform.